Analysis of the van der waals cubic equation os state: from classical thermodynamics to statistics (2020)
Nowadays, vapor-liquid equilibrium in chemical engineering is commonly studied and tested by using simulation software that allows engineers to build up designs, advances and new researches avoiding the thrilling molecular thermodynamic analysis from its foundations, because computing packages such as Aspen® or CHEMCAD® have already included the most of the available equations of state (EoS), which suit depending on the studied system. Nevertheless, the major development of new and better correlations to predict and subsequently model the vapor-liquid equilibrium could be halted by the recent computational chemical engineering,for that reason,in this paper, a procedural demonstration of how the Van der Waals (VdW) equation —the most famous and resulting EoS for years—is stated and developed from the point of view of both classic and statistical thermodynamics. A detailed phenomenological and mathematical description is showed, including a numerical case of study.